2017
DOI: 10.1080/10773525.2018.1450923
|View full text |Cite
|
Sign up to set email alerts
|

Emerging health risks from agricultural intensification in Southeast Asia: a systematic review

Abstract: BackgroundAgricultural intensification is having profound impacts on food security and rural livelihoods; however, concerns remain about the potential implications on public health.ObjectivesWe aim to examine and synthesize the evidence for human health risks of agricultural intensification in Southeast Asia.MethodsWe conducted a systematic review of peer-reviewed articles published between January 2000 and December 2015 from two electronic databases (PubMed, CAB Direct).ResultsA total of 73 relevant studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…In addition, there is a growing body of research suggesting that families engaged in poultry husbandry exhibit an increased risk for carriage of AMR bacteria and diarrheal pathogens [ 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 ]. Also, AMR bacterial carriage in humans via foodborne transmission remains a risk in resource limited settings that lack biosafety regulations in abattoir or retail markets [ 50 , 219 , 220 , 221 ]. Clinical reports of AMR carriage in humans have also been linked to poultry products [ 222 , 223 , 224 , 225 ].…”
Section: Eco-epidemiology Of Poultry Production: a Framework For Ementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a growing body of research suggesting that families engaged in poultry husbandry exhibit an increased risk for carriage of AMR bacteria and diarrheal pathogens [ 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 ]. Also, AMR bacterial carriage in humans via foodborne transmission remains a risk in resource limited settings that lack biosafety regulations in abattoir or retail markets [ 50 , 219 , 220 , 221 ]. Clinical reports of AMR carriage in humans have also been linked to poultry products [ 222 , 223 , 224 , 225 ].…”
Section: Eco-epidemiology Of Poultry Production: a Framework For Ementioning
confidence: 99%
“…More importantly, AMR remains critically understudied within the context of LMICs [ 48 , 49 ]. In resource-limited settings, which comprise the majority of LMIC poultry farming systems, poultry production commonly occurs among small-scale, family operations with limited biosecurity due to constraints in hygiene and sanitation [ 50 , 51 , 52 , 53 ]. Additionally, to facilitate economic growth, developmental organizations often promote the intensive small-scale poultry farming [ 39 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 Farmers typically do not use self-protective behaviors when using chlorpyrifos and most are directly exposed, leading to symptomatic illness. 5 In this study, an occupational health education program based on the theory of the health belief model for behavior modification was used to study safety behaviors and decrease health effects.…”
Section: Introductionmentioning
confidence: 99%
“…In China alone, heavy metal contamination may result in a reduction of more than 10 million tonnes of food supplies each year (FAO, 2015). Many studies have shown the existence of high levels of organochlorines in vegetables and other food products (Lam, Pham and Nguyen-Viet, 2017).…”
Section: Trends In Developing Countriesmentioning
confidence: 99%